2008
DOI: 10.1073/pnas.0710931105
|View full text |Cite
|
Sign up to set email alerts
|

ICA512 signaling enhances pancreatic β-cell proliferation by regulating cyclins D through STATs

Abstract: Changes in metabolic demands dynamically regulate the total mass of adult pancreatic ␤-cells to adjust insulin secretion and preserve glucose homeostasis. Glucose itself is a major regulator of ␤-cell proliferation by inducing insulin secretion and activating ␤-cell insulin receptors. Here, we show that islet cell autoantigen 512 (ICA512)/IA-2, an intrinsic tyrosine phosphatase-like protein of the secretory granules, activates a complementary pathway for ␤-cell proliferation. On granule exocytosis, the ICA512 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 55 publications
1
60
0
Order By: Relevance
“…Previous studies have shown that the deletion of IA-2 or phogrin gene or in combination in mice resulted in mild impairment of GSIS but did not affect ␤-cell mass (19 -21). However, more recent studies have suggested that islets from double knockout mice failed to show any secretion defect (45), and ␤-cell regeneration was reduced in partially pancreatectomized ICA512 (IA-2) knockout mice (46). Therefore, it is possible that the alteration in GSIS in knockout mice is indirect and that ␤-cell mass is recovered by compensatory function of other genes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the deletion of IA-2 or phogrin gene or in combination in mice resulted in mild impairment of GSIS but did not affect ␤-cell mass (19 -21). However, more recent studies have suggested that islets from double knockout mice failed to show any secretion defect (45), and ␤-cell regeneration was reduced in partially pancreatectomized ICA512 (IA-2) knockout mice (46). Therefore, it is possible that the alteration in GSIS in knockout mice is indirect and that ␤-cell mass is recovered by compensatory function of other genes.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of gut-specific ia2 expression reveals a role of IA-2 for modulating both exon SGs are distributed to the plasma membrane when hormones are secreted, then enter into endosomes (or related organelles), and recycle back to SGs. Other reports have proposed that upon insulin secretion in β-cells, IA-2 protein is cleaved by calpain at the site specific to IA-2 [42] but absent in IA-2β [40], and the PTP-containing fragment then enters into the nucleus [43,44]. Although an almost identical fragment (~40 kDa) has been found in the bovine pituitary extracts [10], it remains to be elucidated whether the calpainmediated cleavage similarly occurs in physiological conditions and whether the cleaved transmembrane protein (~30 kDa) is recycled back to SGs.…”
Section: +mentioning
confidence: 99%
“…In this case, scrupulous attention should be paid to the possibility that the stable clone obtained such a potency independent of IA-2, because MIN6 cells are heterogenous in hormone contents [52] and the insulin content per cell is changeable during the cloning steps [27,53,54]. On the other hand, Mziaut et al has demonstrated that insulin gene transcription is promoted by prolonging STAT5 activity through the action of calpain-cleaved IA-2 tail [44], although this retrograde pathway does not seem to apply to IA-2β. Taken together with the results by DKO islets [49], these data partly support the idea that IA-2 and IA-2β contribute to the maintenance of insulin content presumably through regulating expression of insulin and/or SG-associated proteins in pancreatic β-cells.…”
Section: Physiological Function Of Ia-2 Family Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…T4 polynucleotide kinase was obtained from New England Biolabs (Ipswich, MA). [␥- 32 P]ATP (specific activity 3000 Ci/mmol) was from MP Biomedicals (Irvine, CA). [ 3 H]Thymidine (specific activity 20 Ci/mmol) was obtained from PerkinElmer Life Sciences.…”
mentioning
confidence: 99%